Mechanistic Probing of Encapsulation and Confined Growth of Lithium Crystals in Carbonaceous Nanotubes (Adv. Mater. 51/2021). Issue 51 (22nd December 2021) - Wei, Ping; Cheng, Yong; Yan, Xiaolin; Ye, Weibin; Lan, Xiangna; Wang, Lina; Sun, Jingjie; Yu, Zhiyang; Luo, Guangfu; Yang, Yong; Rummeli, Mark H.; Wang, Ming‐Sheng
Abstract : Anode Materials In article number 2105228, Ming‐Sheng Wang and co‐workers reveal the encapsulation mechanism and confined growth kinetics of lithium crystals in carbonaceous nanotubes by in situ transmission electron microscopy. Unusual Li nanostructures such as 2D membranes and multi‐crystal nanowires are discovered. Importantly, sufficient nitrogen/oxygen doping or pre‐lithiation would be critical for the carbon hosts to reliably encapsulate Li metal in a battery anode.